Hemocyanin-derived phenoloxidase reaction products display anti-infective properties. (September 2018) - Coates, Christopher J.; Talbot, James
Abstract: Hemocyanin is a multi-functional protein located in the hemolymph (blood) of certain arthropods and molluscs. In addition to its well-defined role in oxygen transport, hemocyanin can be converted into a phenoloxidase-like enzyme. Herein, we tested the antimicrobial properties of horseshoe crab ( Limulus polyphemus ) hemocyanin-derived phenoloxidase reaction products using broad ranges of phenolic substrates (e.g. l -DOPA) and microbial targets (Gram-positive/negative bacteria, yeast). The enzyme-catalysed turnover of several substrates generated (by)products that reduced significantly the number of colony forming units. Microbicidal effects of hemocyanin-derived phenoloxidase were thwarted by the inhibitor phenylthiourea. Data presented here further support a role for hemocyanin in invertebrate innate immunity. Highlights: Hemocyanin can accommodate diverse diphenolic substrates. Hemocyanin oxidises diphenols into antimicrobial, reactive quinones. Chelicerate hemocyanin is a contributing factor to melanogenesis. Hemocyanin catalytic efficiency correlates broadly with antimicrobial potential. Horseshoe crab hemocyanin is an integral component of innate immunity.